Analysis of selected elements of knowledge management in the context of the size of the enterprise and the specifics of its activity - Prusak Rafał (Management, 2019)
Proper, effective knowledge management is possible only through the implementation of mechanisms and systems tailored to the specifics of the company’s operations and the nature and quantity of its resources. Drawing from the experience of others is advisable, however, to some extent difficult due to the specific uniqueness of many elements of knowledge management in enterprises resulting, for example, from the size of the organization. The study attempts to identify characteristic features of the solutions used in Poland, depending on the size of the enterprise and the nature of its activities. The survey used a questionnaire, which was addressed to the representatives of the top management of 105 enterprises. Based on the obtained results, the characteristics of the identified phenomena and trends were characterized and the limitations of the conducted study were indicated.